Airborne Radioactivity in Hot Lab of Nuclear Medicine - Ferdous, J.; Sharmin, N.; Begum, A.; Begum, A. (Journal of Scientific Research, 2017)
In this study, identification and measurement of gamma emitting radionuclides contaminant in air inside the hot lab at the Institute of Nuclear Medicine have been carried out. Air particulate collection has been performed by suction of indoor air through filter paper using Staplex air sampler. The radioactivities of Pb-212, Pb-214, Ac-228, Bi-214, K-40, I-131 and Tc-99m captured by the filter paper were assessed using gamma-ray spectrometry. The observed activities of natural radionuclides in air samples ranged from 0.59 to 295 mBq/m3 with average 143±0.003 mBq/m3 for Pb-212; 13.55 to 1911 mBq/m3 with average 402±0.007 mBq/m3 for Pb-214; 0.69 mBq/m3 to 571 mBq/m3 with average 57.33±0.009 mBq/m3 for Ac-228; 7.85 to 2192 mBq/m3 with average 543±0.014 mBq/m3 for Bi-214 and from 9.89 mBq/m3 to 256 mBq/m3 with average 92.9±0.052 mBq/m3 for K-40. The activities of artificial radionuclides in air filter ranged from 0.19 to 60.67 mBq/m3 with average 6.4±0.0 mBq/m3 for I-131; 0.25 to 40.27 mBq/m3 with average 4.17±0.0 mBq/m3 for Tc-99m. The activity of I-131 is compared with the reported values of other countries of the world. This demonstrated that the work place condition is satisfactory and the level of protection provided to the worker is sufficient.